Reference in-vitro dataset for inertial-sensor-to-bone alignment applied to the tibiofemoral joint - Ive Weygers (Nature Portfolio, 2021)
Measurement(s) marker trajectory • anatomical landmark • Inertia Technology Type(s) optical motion capture system • computed tomography • inertial measurement device Factor Type(s) movement plane • movement duration • movement excitation • tibiofemoral flexion range of motion Sample Characteristic - Organism Homo sapiens Sample Characteristic - Environment cadaver Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14987013